The effects and use of negative pressure wound therapy - a set of case reports - Brzulová, L; Škach, J; Kocmanová, K; Škaryd, A; Hromádka, P (Rozhledy v chirurgii, 2020)
Modern medicine offers a wide spectrum of wound healing resources for acute or chronic wounds. Negative pressure wound therapy (NPWT) is a very effective method, allowing complicated defects and wounds to heal. The basic set is usually provided with various special accessories to facilitate the use and support safe application of NPWT to high-risk tissue. Selected case reports are presented herein to document the special use and combinations of materials in negative pressure wound therapy.
Keywords: wound healing − pressure wound therapy − case reports; terapie ran pomocí řízeného podtlaku; hojení ran; Wound Healing; Negative-Pressure Wound Therapy